Parallel Bending Strength Characterisation of Malaysian Bambusa Vulgaris Bamboo Culms - Hon Loong, Alvin Chin; Kamarudin, Mohd Khairul; Shahid, Khairul Anuar; Sahol Hamid, Yazmin; Mansor, Hazrina; Ahmad, Zakiah (International Journal of Integrated Engineering, 2026)
Bamboo has been utilized for decades due to its versatility and environmental benefits, making it increasingly significant in addressing modern sustainability challenges. Despite Bambusa vulgaris being one of the best bamboo species globally, limited research has been conducted on its natural form, particularly regarding its physical and mechanical properties. Most studies focus on engineered bamboo products, while natural bamboo’s characteristics remain underexplored. This study focuses on analysing Bambusa vulgaris sourced from the northern (BVB) and middle regions (BVK) of Malaysia, assessing its suitability for structural use through 4-point-bending tests conducted on 85 treated samples in accordance with ISO 22157. Specimens were tested across three sections along the culm length (top, middle, bottom) to investigate variations in mechanical and physical properties. The study found that Bambusa vulgaris exhibits significant variations in physical and mechanical properties across regions and culm sections. The bottom section had the largest diameter and thickest walls, while the top was smallest, with both regions showing moisture content below 12%. Mechanical testing indicated that BVB outperformed BVK in bending moment, strength, and stiffness, with both showing similar failure modes of longitudinal and transverse cracks. Positive correlations between diameter and ultimate strength, as well as bending stiffness and linear mass, highlight its potential as a sustainable structural material in Malaysia.